Stimulation of c-Jun/AP-1-Activity by the Cell Cycle Inhibitor p57Kip2 - Kullmann, Michael Keith; Pegka, Fragka; Ploner, Christian; Hengst, Ludger (Frontiers in Cell and Developmental Biology, 2021)
p57 is a member of the Cip/Kip family of cell cycle inhibitors which restrict the eukaryotic cell cycle by binding to and inhibiting cyclin/CDK complexes. They are considered as tumor suppressors and inactivating genomic mutations of p57 are associated with human overgrowth disorders. Increasing evidence suggests that p57 controls additional cellular processes beyond cell cycle control such as apoptosis, cell migration or transcription. Here we report that p57 can stimulate AP-1 promotor activity. While transactivation by c-Jun is strongly activated by p57, it did not enhance c-Fos induced transcription. This indicates that c-Jun is the target of p57 in the canonical AP-1 heterodimeric transcription factor. We could detect endogenous p57/c-Jun containing complexes in cells by co-immunoprecipitation. The strong stimulation of c-Jun activity is not the consequence of activating phosphorylation in the transactivation domain (TAD) of c-Jun, but rather due to negative interference with c-Jun repressors and positive interference with c-Jun activators. In contrast to full-length p57, the amino- and carboxyterminal domains of p57 are insufficient for a significant activation of c-Jun induced transcription. When expressed in presence of full length p57, the p57 C-terminus abrogated and the N-terminus enhanced c-Jun activation. This indicates that the C-terminus may bind and sequester a putative activator of c-Jun, whereas the N-terminus may sequester a c-Jun repressor. Interestingly, the p57 aminoterminus is sufficient for binding to the two c-Jun repressors HDAC1 and HDAC3. These data are consistent with a model of c-Jun activation where p57 is a part of large nuclear remodeling/transcription complexes. p57 might stimulate transcription by inhibiting transcription repressor proteins like HDACs via its N-terminus and/or attracting transcription activators through its C-terminus. These data suggest that in addition to its role as a CDK inhibitor and tumor suppressor, p57 may also exert tumor promoting functions by activation of the proto-oncoprotein c-Jun.